El poder liberatorio y curso ilegal de las criptomonedas y los actos criminales en el Ecuador - Granja Martínez, Lorena Nathaly (2025)
The present study deals with ‘the liberatory power and illegal course of cryptocurrencies and criminal acts in Ecuador’, which analyses the influence and challenges that cryptocurrencies present in the legal and criminal context. As cryptocurrencies such as Bitcoin gain popularity, they have developed as tools for both financial innovation and criminal activities. The research focused on two main aspects: the liberatory power of cryptocurrencies and their use in illegal activities. In order to meet the stated objective, a critical legal analysis was developed on the incidence of the liberatory power and illegal course of cryptocurrencies in the commission of criminal acts in Ecuador. A qualitative approach was used to understand the social perception and use of the liberatory power of cryptocurrencies in the Ecuadorian context, in addition to exploring the illegal aspects associated with them. The research was based on judicial sources, including the analysis of two recent cases, involving the purchase and sale of cryptocurrencies and their relationship with criminal acts in Ecuador. The results conclude that criminal acts such as fraud are directly related to the use of cryptocurrencies. Despite the fact that cryptocurrencies are not authorized or regulated by any specific legislation in Ecuador, the need to establish stricter regulations to control their use and mitigate the associated risks is evident.